2015
DOI: 10.1002/chem.201502706
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of an Intramolecular CF3‐Group Shift in the Reactions of α‐Bromoenones with 1,2‐Diamines

Abstract: The reactions of trifluoromethylated 2-bromoenones and N,N'-dialkyl-1,2-diamines have been studied. Depending on the structures of the starting compounds, the formation of 2-trifluoroacetylpiperazine or 3-trifluoromethylpiperazine-2-ones was observed. The mechanism of the reaction is discussed in terms of multistep processes involving sequential substitution of bromine in the starting α-bromoenones and intramolecular cyclization of the captodative aminoenones as key intermediates to form the target heterocycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The latter then undergoes a 1,2‐shift of the CF 3 group to finally give piperazinones 3 6. In the case of N , N′ ‐dicyclopropyl ethylenediamine, an alternative sequence is preferable, as confirmed by calculations 6b. Instead of intermolecular nucleophilic substitution to form intermediate B with a second molecule of diamine, cyclization takes place through intramolecular nucleophilic substitution of bromine (Scheme ).…”
Section: Introductionmentioning
confidence: 84%
“…The latter then undergoes a 1,2‐shift of the CF 3 group to finally give piperazinones 3 6. In the case of N , N′ ‐dicyclopropyl ethylenediamine, an alternative sequence is preferable, as confirmed by calculations 6b. Instead of intermolecular nucleophilic substitution to form intermediate B with a second molecule of diamine, cyclization takes place through intramolecular nucleophilic substitution of bromine (Scheme ).…”
Section: Introductionmentioning
confidence: 84%
“…In order to develop methods for the preparation of six‐membered aza‐heterocycles, non‐fluorinated enones 1 were treated with symmetric dimethylethylenediamine (DMEDA). We showed that in this case complex reaction mixtures were formed, usually containing fragmentation and unidentified products (Scheme ) …”
Section: Reactions With Nucleophilesmentioning
confidence: 91%
“…However, the expected trifluoroacetylpiperazines 12 were obtained only with the dicyclopropyl derivative of ethylenediamine. To our great surprise, in all other cases in which bromoenones reacted with N , N′ ‐dialkylethylenediamines the isomeric piperazinones 11 were isolated in good to excellent yields , . It should be emphasized that the piperazinones obtained are a very rare type of heterocycles and that, to the best of our knowledge, no other methods for their assembly are yet known.…”
Section: Reactions With Nucleophilesmentioning
confidence: 99%
See 1 more Smart Citation
“…The conjugate nucleophilic addition to functionalized enones is a straightforward method for the carbon–carbon or carbon–heteroatom bond formation. In this context, we recently demonstrated that trifluoromethylated α‐bromoenones are excellent Michael acceptors and valuable starting materials in the reaction with nitrogen‐bearing mono‐ or binucleophiles for assembly of a diversity of trifluoromethylated linear as well as carbo‐ and heterocyclic derivatives . These enones are ambivalent bielectrophiles bearing electrophilic centers at the carbonyl function and at the olefinic β‐carbon; therefore, they can react with nucleophiles either in 1,2‐ or 1,4‐addition mode.…”
Section: Introductionmentioning
confidence: 99%